EXPRESSION OF VESICULAR GLUTAMATE TRANSPORTERS IN TRANSIENT RECEPTOR POTENTIAL MELASTATIN 8 (TRPM8)-POSITIVE DENTAL AFFERENTS IN THE MOUSE - Kim, Y. S. (Neuroscience, 2015)
Transient receptor potential melastatin 8 (TRPM8) is activated by innocuous cool and noxious cold and plays a crucial role in cold-induced acute pain and pain hypersensitivity. To help understand the mechanism of TRPM8-mediated cold perception under normal and pathologic conditions, we used light microscopic immunohistochemistry and Western blot analysis in mice expressing a genetically encoded axonal tracer in TRPM8-positive (+) neurons. We investigated the coexpression of TRPM8 and vesicular glutamate transporter 1 (VGLUT1) and VGLUT2 in the trigeminal ganglion (TG) and the dental pulp before and after inducing pulpal inflammation. Many TRPM8+ neurons in the TG and axons in the dental pulp expressed VGLUT2, while none expressed VGLUT1. TRPM8+ axons were dense in the pulp horn and peripheral pulp and also frequently observed in the dentinal tubules. Following pulpal inflammation, the proportion of VGLUT2+ and of VGLUT2+/TRPM8+ neurons increased significantly, whereas that of TRPM8+ neurons remained unchanged. Our findings suggest the existence of VGLUT2 (but not VGLUT1)-mediated glutamate signaling in TRPM8+ neurons possibly underlying the cold-induced acute pain and hypersensitivity to cold following pulpal inflammation.